Novel gold nanoparticle substrates based on Surface Enhanced Raman Spectroscopy (SERS) and optimization of their enhancement and reproducibility properties - Chan, Yew Tow. (2010)
First reported in 1977 SERS has since been widely studied. Crucial for the fabrication of quality SERS substrate with reliably reproducible results is the consistent and homogenous distribution of hot spots which form at the convergence of two nanoparticles. Presence of these hot spots accounts for the enhancement of SERS intensity. Pioneered by Michael J. Natan in 1995, SERS substrate fabrication based on self-assembly of metal colloid monolayers has been extensively practiced. Adopting a similar approach, this project introduces an improved design in SERS substrate fabrication by changing the geometrical parameters of gold nanoparticles (small gold nanoparticles on an array of larger particles – substrate LG0) and employing established thiol chemistry as linker molecules between depositions of gold colloids on glass surface. Three different substrates are prepared each with a unique structural conformation: gold monolayer (G0), gold bilayer (G1) and a novel structure where smaller gold nanoparticles are deposited onto a larger gold monolayer (LG0). To test for their characteristic signal enhancement and reproducibility, SERS measurement of adsorbed Raman reporter molecules were recorded for all three substrates follow by comparison of their signal intensities and the calculated error bars. Of the three, substrate LG0 is hypothesized to have superior enhancement and reproducibility properties.